Enhanced production of nattokinase from UV mutated Bacillus sp. - V. Mohanasrinivasan; C. Subathra Devi; Ritusree Biswas; Falguni Paul; Mohor Mitra; E. Selvarajan; V. Suganthi (Bangladesh Pharmacological Society, 2013)
In the recent years, nattokinase is one of the most-often employed among the several thrombolytic agents used clinically, particularly because of its lower cost comparing to other thrombolytic agents. In the present research work, Bacillus sp. was isolated from the heterogeneous microbial population present in the soil sample and screened for the production of nattokinase. The production of the enzyme was carried out using two different media (with and without shrimp shell substrate). Nattokinase activity (clot buster) was determined by using a modified Holmstorm method. The production strain SFN01 was improved by random mutagenesis (UV radiation) and the enzyme activity was checked with the enzyme produced by wild strain. The mutated strains had exhibited a higher clot lysis activity in which 1 unit of the enzyme completely lyses 1 mL of human blood when compared to the wild strain. Nattokinase produced by SFN showed a retention time of 10.6 min in RP-HPLC chromatogram.